Effectiveness of progressive muscle relaxation program on cancer related fatigue in hepatocellular carcinoma patients receiving transarterial chemoembolization - Wairit, Sirikanya; Khamboon, Thidarat; Khunrat, Jaruwat (NU Journal of Nursing and Health Sciences, 2021)
The purpose of this quasi-experimental research was to study fatigue before and after receiving a progressive muscle relaxation program among patients with hepatocellular carcinoma (HCC) who were undergoing transarterial chemoembolization (TACE) and to compare the fatigue post-TACE between the control group and experimental group. The subjects consisted of 54 HCC patients receiving TACE at Naresuan University Hospital, Phitsanulok. Selected by purposive sampling technique, 27 patients were control group who received routine nursing care and the other 27 patients were in the experimental group who received progressive muscle relaxation program. The research instruments for progressive muscle relaxation program are as follows: 1.) fatigue experience assessment before TACE, 2.) fatigue management strategies including fatigue education session, progressive muscle relaxation teaching and training session, 4 weeks of progressive muscle relaxation self-practicing, and telephone follow up periodically, 3.) fatigue outcome assessment after TACE. Data was collected by using fatigue assessment form and Thai version of Revised Piper Fatigue Scale. Statistical techniques used in data analysis were Two-way repeated measure ANOVA and simple main effects: Bonferroni, frequency distribution, percentage, Chi-Square Test, Fisher's exact test, Independent t-test, and Mann-Whitney U test at the significant level of .05. The major findings were 1) Interaction between treatment and time had an effect on the mean total fatigue score of HCC patients receiving TACE with statistical significance at .01 (F(2.22, 57.7) = 12.46, p = .000), 2) there was no statistically significant difference of the mean total fatigue score between pre and post-TACE day 5 (p > .05) in the experimental group, but the mean total fatigue score post-TACE day 14 and 28 in the experimental group was lower than pre- TACE (p < .01) 3) the mean total fatigue score post-TACE day 5, 14, and 28 in the experimental group had statistically lower than the control group at .05 level. According to the study, the progressive muscle relaxation program was found to be efficient in HCC patients undergoing TACE. It can be used as a guideline for nurse to manage patient’s fatigue.